Β-Arrestin as a Therapeutic Target in Heart Failure. Issue 5 (September 2021) - Boussi, Leora; Frishman, William H.
Abstract : Heart failure is a major source of morbidity and mortality, driven, in part, by maladaptive sympathetic hyperactivity in response to poor cardiac output. Current therapies target β-adrenergic and angiotensin II G protein-coupled receptors to reduce adverse cardiac remodeling and improve clinical outcomes; however, there is a pressing need for new therapeutic approaches to preserve cardiac function. β-arrestin is a multifunctional protein which has come under analysis in recent years as a key player in G protein-coupled receptor signal transduction and a potential therapeutic target in heart failure. β-arrestin attenuates β-adrenergic and angiotensin II receptor signaling to limit the deleterious response to excessive sympathetic stimulation while simultaneously transactivating cardioprotective signaling cascades that preserve cardiac structure and function in response to injury. β-arrestin signaling may provide unique advantages compared to classic heart failure treatment approaches, but a number of challenges currently limit clinical applications. In this review, we discuss the role and functions of β-arrestin and the current attempts to develop G protein-coupled receptor agonists biased towards β-arrestin activation. Furthermore, we examine the functional diversity of cardiac β-arrestin isotypes to explore key considerations in the promise of β-arrestin as a pharmacotherapeutic target in heart failure.